Functional Genomics Methods and Protocols - Kaufmann, Michael; Klinger, Claudia; Savelsbergh, Andreas (Methods in Molecular Biology, 2017)
Reflecting developments in genome editing, this third edition volume fully updates a collection of key techniques for the study of functional genomics. The book is broken up into sections on bioinformatics, DNA, RNA, and protein analysis, as well as a closing section entitled "From Genotype to Phenotype." Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Updated and authoritative, Functional Genomics: Methods and Protocols, Third Edition seeks to aid scientists in establishing or extending technologies and techniques in their laboratories